Sodelovanje učiteljev pri razreševanju problemov na delovnem mestu - Mateja Pšunder, Mateja (Revija za elementarno izobraževanje, 2012)
Teacher cooperation in solving workplace problems. Cooperation between teachers can be regarded as an important factor in teachers’ professional development and as a prerequisite for continuous school development. In the theoretical part of the article, the importance of teachers’ cooperation with other teachers and professionals is discussed. We point out that cooperation is particularly important when teachers encounter problems or find themselves in distress. The aim of the empirical part of the article is to establish what problems teachers face in their work and how they resolve them. Research has shown that teachers most often face problems with individual students and disciplinary problems. These difficulties are often resolved through cooperation with other people. More than half of the teachers report having more than one person to whom they can turn to for support and help in problem solving. The study also reveals that teachers would like their cooperation with the following persons or groups was more frequent: colleague teachers who teach the same subject; teachers who teach a particular student; school counsellors; teaching staff; school staff and parents.